2017
DOI: 10.1080/17538157.2017.1363761
|View full text |Cite
|
Sign up to set email alerts
|

Perceived usefulness and perceived ease of use of electronic health records among nurses: Application of Technology Acceptance Model

Abstract: This study adds to the growing body of knowledge on issues related to the acceptance of technology in the health informatics field, focusing on nurses' acceptance of EHRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
91
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 23 publications
15
91
1
4
Order By: Relevance
“…Specifically, they included personal, organisation or system factors such as age, perceived usefulness and organisational support. Previous studies have also shown the influence of these factors on healthcare professionals’ perception of EHR 21 50–52. At the individual level, Duarte and Azevedo51 showed that younger professionals in Brazil were more satisfied with EHRs than older counterparts which is similar to the findings of this systematic review.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, they included personal, organisation or system factors such as age, perceived usefulness and organisational support. Previous studies have also shown the influence of these factors on healthcare professionals’ perception of EHR 21 50–52. At the individual level, Duarte and Azevedo51 showed that younger professionals in Brazil were more satisfied with EHRs than older counterparts which is similar to the findings of this systematic review.…”
Section: Discussionsupporting
confidence: 87%
“…Although nurses change their time allocation, they do a more hourly intervention. In the use of EHR that nurses with advanced skills in computer applications feel that the system is easy to use, advanced users will find the system more useful regarding patient benefits, cost reduction, and improving workflow (12).…”
Section: Resultsmentioning
confidence: 99%
“…The use of a portable computer is considered to be more time-saving, energy efficiency because the data is directly inputted alongside the patient, so there will be no missing data, and no need to spend time in inputting data in the nurse's room (12). The infusion management system, this system saving time and space for other nursing activities, avoid back and forth, workload and work intensity decreases, and improving patient safety related to patient infusion conditions (14).…”
Section: Discussionmentioning
confidence: 99%
“…The result of these studies shows that the ease from using EHR is influenced by nursing experience and ability to operate computers. This research gives addition perspectives on issues related to technology accepted in health care provider focusing on nurses acceptance of EHR (12) . Considering usability requirements in the design of nursing information systems will lead to the efficient and effective use of these systems (13).…”
Section: Electronic-based Nursing Care Documentation For Improving Thmentioning
confidence: 99%
“…The study aims to determine whether the substantial national investment in EHRs over the past five years is associated with higher quality, provides more efficient hospital care, and in particular, focuses on time-related effects. 12 Tubaishat, (2017) SIMPRO increases the quality, completeness, relevance, and sustainability, and functions of the decision, which supports system in delivering nursing care as well as in nursing management. SIMPRO also provides services and roles in planning, organizing, actuating, staffing, and controlling (POSAC) management.…”
Section: Conflicts Of Interestmentioning
confidence: 99%